Current update of laboratory molecular diagnostics advancement in management of colorectal cancer (CRC) - Pang, Siew Wai *; Awi, Noel Jacques *; Armon, Subasri; Lim, Wendy Wan-Dee; Low, John Seng-Hooi; Peh, Kaik-Boo; Peh, Suat Cheng *; Teow, Sin Yeang * (MDPI, 2019)
Colorectal cancer (CRC) continues to be one of the most common cancers globally. The incidence has increased in developing countries in the past few decades, this could be partly attributed to aging populations and unhealthy lifestyles. While the treatment of CRC has seen significant improvement since the advent of target-specific therapies and personalized medicine, CRC is oftentimes detected at late or advanced stages, thereby reducing the efficacy of treatment. Hence, screening for early detection is still the key to combat CRC and to increase overall survival (OS). Considering that the field of medical diagnostics is moving towards molecular diagnostics, CRC can now be effectively screened and diagnosed with high accuracy and sensitivity. Depending on the tumor genotype and genetic profile of the individual, personalized treatments including tyrosine kinase inhibitor therapy and immunotherapy can be administered. Notably, there can be no one single treatment that is effective for all CRC patients due to the variation in tumor genetics, which highlights the importance of molecular diagnostics. This review provides insights on therapeutic modalities, molecular biomarkers, advancement of diagnostic technologies, and current challenges in managing CRC.